Mechanical Properties of Glassy Nanopillars: A Comparative, Computational Study of Size Effects in Nanoglasses and Homogeneous Bulk Glasses - Adjaoud, Omar; Albe, Karsten (Frontiers in Materials, 2020)
We study the mechanical properties of nanoglass (NG) nanopillars with diameters ranging from 4.5 to 54 nm by means of molecular dynamic simulations and compare the results with those obtained for nanopillars prepared from homogeneous glasses. NG nanopillars of two different types of glasses, namely, Cu64Zr36 and Pd80Si20, were cut from samples prepared by nanoparticle consolidation. The influence of nanopillar diameter on the deformation behavior and strain localization is investigated. Moreover, cyclic loading is used to explore the origin of stress overshoots in the stress–strain curves of NGs. Finally, from the calculated properties, a deformation map for NG and homogeneous glass nanopillars is derived.